Complete genome sequence of "Thioalkalivibrio sulfidophilus" HL-EbGr7. Issue 1 (January 2011) - Muyzer, Gerard; Sorokin, Dimitry; Mavromatis, Konstantinos; Lapidus, Alla; Clum, Alicia; Ivanova, Natalia; Pati, Amrita; d'Haeseleer, Patrick; Woyke, Tanja; Kyrpides, Nikos
Abstract "Thioalkalivibrio sulfidophilus " HL-EbGr7 is an obligately chemolithoautotrophic, haloalkaliphilic sulfur-oxidizing bacterium (SOB) belonging to theGammaproteobacteria . The strain was found to predominate a full-scale bioreactor, removing sulfide from biogas. Here we report the complete genome sequence of strain HL-EbGr7 and its annotation. The genome was sequenced within the Joint Genome Institute Community Sequencing Program, because of its relevance to the sustainable removal of sulfide from bio- and industrial waste gases.